The Implications of Regulating Zakat to Reduce Income Tax and Make it A Source of Local Revenue in Aceh - Fuadi, Fuadi; Sahara, Siti; Suriyani, Meta (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This study aims to analyze the implications of regulating zakat as a source of local own-source revenue and as a factor in reducing income tax payable in Law Number 11 of 2006 concerning the Aceh Government. These two norms complement each other and are implemented simultaneously; thus, state revenue from taxes does not decrease. It means that zakat as a deduction from income tax is covered by zakat as a source of local own-source revenue. However, the regulation for zakat as a deduction from income tax cannot be enforced due to regulatory synchronization reasons. This study is normative legal research using a statutory and regulatory approach. The data described is normative data such as laws, qanuns and other legal regulations. This study concludes that the regulation of zakat as regional original income incorporates zakat into the state financial governance system managed by Baitul Mal. There are several consequences arising from the issue. Zakat deposited into the Regional Treasury is recorded by the Regional General Treasurer in a separate account whose designation is Sharia-related. Crimes related to Zakat cannot be classified as ordinary embezzlement crimes but as acts of corruption. These discrepancies in norms lead to legal ambiguity, which, in turn, infringes upon the hierarchy of laws and regulations, disrupting the legal order. To address this issue, a vertical harmonization process is necessary, involving the revision of the Aceh Qanun about Baitul Mal.